Intrauterine Exposure to Arsenic Affect Infant Development - Tofail, Fahmida; Hamadani, Janna D; Hakim, Maliha; Ali, Zahed; Ahmed, AZ Tofail (Bangladesh Journal of Neuroscience, 2009)
The ICDDR,B Child Development Unit (CDU) conducted a longitudinal observational study on a sample of 1562 pregnant mothers in Matlab, Bangladesh, to examine the intrauterine effects of arsenic on infants. Drinking water consumed by the mothers during their pregnancy was assessed for arsenic concentration using atomic-absorption spectroscopy. Infants were assessed for cognitive and psychomotor development at the age of 7 months. Sixty-three percent of all functioning tube wells had arsenic contamination above 50?g/L. Infants whose mother drank water from wells with >50?g/ L of arsenic had slightly lower developmental scores than those whose mother's drinking water had lower arsenic levels. While the clinical importance and long-term implications of these developmental differences need to be determined, these results provide further evidence of the urgent need to reduce the arsenic contamination in Bangladesh. DOI: http://dx.doi.org/10.3329/bjn.v24i1.3042 Bangladesh Journal of Neuroscience 2008; Vol. 24 (1) :55-59